The European Union: how to assign the functions of government - MARÈ, M.; SARCINELLI, M. (PSL Quarterly Review, 2013)
Recent progress towards the construction of the European Union slowed down a little with the exchange rate problems of 1992 and 1993. Central elements in the construction strategy are extending the internal market and building institutions with government functions at the supranational level. A review is undertaken of the economic theory of multi-level government finance, the optimal assignment of fiscal responsibilities to various government tiers, and the general applicability of these theories to the European Union. JEL Codes: F02, F15